Tariff Passthrough at the Border and at the Store : Evidence from US Trade Policy - Cavallo, Alberto (IMF Working Papers; Working Paper ;, 2019)
We use micro data collected at the border and at retailers to characterize the effects brought by recent changes in US trade policy - particularly the tariffs placed on imports from China - on importers, consumers, and exporters. We start by documenting that the tariffs were almost fully passed through to total prices paid by importers, suggesting the tariffs' incidence has fallen largely on the United States. Since we estimate the response of prices to exchange rates to be far more muted, the recent depreciation of the Chinese renminbi is unlikely to alter this conclusion. Next, using product-level data from several large multi-national retailers, we demonstrate that the impact of the tariffs on retail prices is more mixed. Some affected product categories have seen sharp price increases, but the difference between affected and unaffected products is generally quite modest, suggesting that retail margins have fallen. These retailers' imports increased after the initial announcement of possible tariffs, but before their full implementation, so the intermediate passthrough of tariffs to their prices may not persist. Finally, in contrast to the case of foreign exporters facing US tariffs, we show that US exporters lowered their prices on goods subjected to foreign retaliatory tariffs compared to exports of non-targeted goods.